Having in mind the philosophy of Keith Donnellan - Almog, Joseph; Leonardi, Paolo (New York ; Oxford : Oxford University Press, 2012)
This volume collects critical essays on the philosophy of Keith Donnellan, one of the founding fathers of contemporary philosophy of language.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Donnellan, Keith